2017
DOI: 10.3892/ol.2017.6284
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the TERT promoter leads to poor prognosis of patients with non-small cell lung cancer

Abstract: Abstract. Mutations in the promoter region of telomerase reverse transcriptase (TERT) and alterations in telomere length (TL) have been the focus of research in various types of cancer. In the present study, the frequency and clinical characteristics of TERT promoter mutations and TL were studied in non-small cell lung cancers (NSCLC). TERT promoter mutations and TL were analyzed in 188 patients using DNA sequencing and the reverse transcription-quantitative polymerase chain reaction, respectively. The TERT pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 23 publications
5
26
0
Order By: Relevance
“…Tumors carrying activating mutations in the TERT promoter region tend to be more aggressive, both in head and neck and other cancer types [12, 2731]. Evidence exists to suggest that these mutations are overrepresented in patients failing their first line of treatment [12].…”
Section: Discussionmentioning
confidence: 99%
“…Tumors carrying activating mutations in the TERT promoter region tend to be more aggressive, both in head and neck and other cancer types [12, 2731]. Evidence exists to suggest that these mutations are overrepresented in patients failing their first line of treatment [12].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to telomere shortening in healthy cells, the majority of cancer cells aberrantly reactivate telomerase to achieve unlimited proliferative potential, one of the hallmarks of cancer [ 65 ]. Indeed, many different human cancer types show mutations in either the promotor region or coding regions of the telomerase catalytic subunit TERT gene [ 23 31 , 66 ]. Also, a wide variety of mouse cancers activate telomerase [ 32 – 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, owing to its ability to confer unlimited proliferative potential, TERT is also found over-expressed and mutated in the vast majority of human cancers including lung cancer where it is thought to allow cancer cell growth by ensuring a minimal telomere length to warrant telomere protection [ 23 31 ]. Telomerase is also upregulated in mouse tumors [ 32 – 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the key events reported are mutations affecting the tumor suppressor gene p53, with a high percentage of CC > TT alterations, which confirms the causative role of solar rays in the etiology of the tumor [ 50 ]. Moreover, Scholz et al identified mutations in the telomerase reverse transcriptase (TERT) gene promoter—a marker of other systemic cancers [ 51 ] and a sign of worse prognosis [ 52 , 53 ]—in 44% of the 48 samples of conjunctival OSSN included in their study [ 54 ]. Finally, hyper-expression of matrix metalloproteinases MMP-9 and MMP-11 and hypo-expression of clusterin seem to be a hallmark in the tumor cell transcriptome [ 55 ].…”
Section: Risk Factors and Pathogenesismentioning
confidence: 99%